2014
DOI: 10.1371/journal.pone.0089123
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology Approach to Understanding the Mechanisms of Action of Traditional Medicine: Bushenhuoxue Formula for Treatment of Chronic Kidney Disease

Abstract: Traditional Chinese medicine (TCM) has unique therapeutic effects for complex chronic diseases. However, for the lack of an effective systematic approach, the research progress on the effective substances and pharmacological mechanism of action has been very slow. In this paper, by incorporating network biology, bioinformatics and chemoinformatics methods, an integrated approach was proposed to systematically investigate and explain the pharmacological mechanism of action and effective substances of TCM. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 148 publications
1
64
0
Order By: Relevance
“…Some of the approaches reviewed below do not go as far as suggesting a direct MoA, although it may for example be unrealistic to expect to be able to de-convolute the mechanism of action of a mix of many compounds, as is the case in Shi et al, 48 where individual components themselves are polypharmacologic. Some of the approaches reviewed below do not go as far as suggesting a direct MoA, although it may for example be unrealistic to expect to be able to de-convolute the mechanism of action of a mix of many compounds, as is the case in Shi et al, 48 where individual components themselves are polypharmacologic.…”
Section: Other Functional Approaches To Moa Elucidationmentioning
confidence: 99%
“…Some of the approaches reviewed below do not go as far as suggesting a direct MoA, although it may for example be unrealistic to expect to be able to de-convolute the mechanism of action of a mix of many compounds, as is the case in Shi et al, 48 where individual components themselves are polypharmacologic. Some of the approaches reviewed below do not go as far as suggesting a direct MoA, although it may for example be unrealistic to expect to be able to de-convolute the mechanism of action of a mix of many compounds, as is the case in Shi et al, 48 where individual components themselves are polypharmacologic.…”
Section: Other Functional Approaches To Moa Elucidationmentioning
confidence: 99%
“…Many studies have been reported to elucidate the molecular mechanism of TCM formulae in systematic view23456789. Compound-target networks were constructed and analyzed in these studies, and the effectiveness of TCM formulae was evaluated at compound level.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic docking and drug-target network analysis is widely applied in these studies23456789, however, the therapeutic effectiveness of TCM formulae is still ascribed to a few number of interactions between individual compounds and key target proteins. As TCMs are prescribed as herbs, compounds from one herb should be considered as a whole and mode of action at herb-level should be noticed.…”
mentioning
confidence: 99%
“…A concept of 'network target' has been proposed to help design and predict the best possible treatments (Li, 2007;Li et al, 2011). The constructed network system can predict the main active components, and their corresponding targets, which can be helpful for the therapeutic applications of complex formulations of traditional medicine (Shi et al, 2014).…”
Section: Network Pharmacologymentioning
confidence: 99%